Protein hydrolysates from fish wastes: nutritional characteristics and its inclusion in diets for Octopus maya - Honorio Cruz-López; Cristina Pascual; Magalli Sanchez; Pedro Domingues; Carlos Rosas; Pedro Gallardo (PLoS ONE, 2025)
The utilization of fish waste protein as an alternative to crab and squid protein presents an important alternative for octopus fattening. During this study, nutritional characteristics of fish protein hydrolysate (FPH) and its inclusion in prepared diets were evaluated on growth performance and enzyme activity of digestive gland of O. maya juveniles. FPH were prepared using fish waste and their nutritional properties were evaluated. Four diets with different levels of FPH (0%, 10%, 15%, and 20%) in substitution for crab meals were fed to octopuses (mean body weight 100 mg) individually distributed for 70 days. Regarding yield, at the end of the hydrolysis period (day 15) the FPH fraction constitutes 67% of the total silage (dried powder). Small peptides were recorded in FPH (< 2.12 DA). Altogether, 17 amino acids were identified on FPH, encompassing nine essential amino acids (EAAs; 182 mg g-1) and eight non-essential amino acids (NEAAs; 427 mg g-1). Also, the free amino acids (FAAs) content was 8.3% of the total amino acids content with the predominance of taurine. Octopuses fed with FPH15 had the highest weight gain (3.06 g), SGR (4.76% day-1), and survival (90%) compared to FPH0. Total alkaline protease activity of octopuses digestive gland was lower in FPH20 (3550 U mg of protein−1) than in the control (5277 U mg of protein−1). Incorporating protein hydrolysate derived from fish waste into prepared diet may offer unique advantages in promoting optimal growth and general physiological well-being for O. maya.